Exploring Teaching Techniques Used In Teaching Reading Comprehension By English Teachers At Madrasah Aliyah Pasangkayu - Putri, Aisyah Kahar; Rofiqoh, Rofiqoh; Mukrim, Mukrim (Syntax Literate, 2021)
This research was aimed at finding out the teaching techniques used in teaching reading comprehension by English teachers from four Madrasah Aliyah at Pasangkayu Regency. MAN Pasangkayu, MA DDI Pasangkayu, MA DDI Kasoloang and MA DDI Darul Ulum. This research applied mix method approach. The respondents of this research were 8 English teachers. The instrument for collecting the data was a questionnaire and interview. Quantitative data were collected and analyzed in the first phase of the research and qualitative data were collected in the second phase. The results reveal that the English teachers use several techniques in teaching reading comprehension such as Scanning Technique, Skimming Technique, SQ3R, Speed Reading, Detailed Reading Strategy, and Collaborative Strategic Reading. The result of the interview showed that the teachers tended to use the Scanning-Skimming technique and SQ3R compared to other techniques. According to them, the Scanning-Skimming technique were two techniques that were very effective for students to use when they did English exams, especially reading texts, they find it easier to get information from a reading text. Meanwhile, SQ3R is a technique that is very good for the benefit of reading intensively. The teachers at Madrasah Aliyah Pasangkayu Regency to upgrade in teaching reading are only some of them who have attended seminars/webinars or training from related agencies or schools. As for their efforts in improving their reading teaching skills, only a few of them were creative to learn independently to find references, hold study groups, review journals, and download videos about teaching reading techniques. Every teacher needs to be more creative for the learning process can be successful.